'Bring us wealth, or keep it among us': The Financial Literature of the Edinburgh Pamphlet War of 1705, and the Capitalisation of the Scottish Economy. Issue 2 (August 2022) - McDiarmid, Andrew
Abstract : The opening years of the 1700s were financially difficult for Scotland. The poor harvests of 1696 and 1697 had pushed up food prices and led to widespread starvation in the country, while coin flowed out to buy much needed imports. The loss of trade and taxation associated with the Nine Years' War (1688–97) exacerbated issues, before the relinquishing of the Scottish colony at Darien compounded the nation's economic problems in the new century. In 1704, a funding deficit then forced the Bank of Scotland to stop cash payments, lending, and discounting. In response to the economic crisis, a body of financial literature emerged from Scotland in 1705 which attempted to improve the situation. This included proposals to address the shortage of coin by debasing existing stocks with copper, schemes to establish land banks and issue a new paper currency on this security, and a proposal for credit secured on the money tied up in the failed Darien scheme. The works emerged from various men, with various models, but all were focused on capitalising the Scottish economy. This article will provide an overview of these works, and will make the case that by the middle of 1705 many of the Scottish parliamentarians tasked with considering these proposals were already predisposed to the idea that a union with England was the solution to Scotland's economic problems. Therefore, despite the revolutionary nature of some of the financial proposals, all were rejected by the administration, as the focus of the Scottish parliament shifted to paving the way for Union.